Variable flow pipework systems : valve solutions, supplement to CIBSE knowledge series KS7 - Parsloe, C. (Chartered Institution Of Building Services Engineers, 2009)
This publication forms a supplement to CIBSE Knowledge Series KS7: Variable flow pipework systems (CIBSE, 2006). It explains how to design re-circulating heating and cooling water systems incorporating variable speed pumps utilising two alternative valve solutions not covered in KS7, these being centralised valve modules and pressure independent control valves (PICVs).
Keywords: Piping.; Pipe fitting.; Water -- Distribution.; Water-supply engineering.; Hydronics.; elektronické knihy; electronic books